Auto-ethnography in Public Policy Advocacy Theory, Policy and Practice - Sinden-Carroll, Louise (Springer Nature Singapore : Imprint: Springer, 2019)
This book explores how public policy advocacy can be used to approach policy issue identification, resolution or, at the least, support the management of wicked policy issues. By describing how this type of advocacy draws on participatory action research, including ethnographic and auto-ethnographic models, this book offers a tool for public policy consumer advocates on how to apply the Human Capabilities Approach to address presenting public policy issues worldwide. By applying these models to the situation of prisoners with hearing loss in New Zealand's prisons, it identifies multiple causal factors for quality-of-life-limiting marginalization, e.g. social barriers (e.g. disability discrimination); environmental limitations (e.g. geographical and those introduced by incarceration); and individual responses in line with negative attitudes - both social and political, including the State's denial of prisoners' right to democratic participation by revoking their right to vote in general elections after sentencing. In addition, two other areas, namely blood safety and broadcast media captioning, are highlighted, showing that the skill of auto-ethnography is transferrable and can be applied to ensure effective consumer advocacy for a diverse range of issues that affect marginalized sectors.